2015
DOI: 10.3892/mmr.2015.4258
|View full text |Cite
|
Sign up to set email alerts
|

Hypericin-mediated photodynamic therapy induces apoptosis in K562 human leukemia cells through JNK pathway modulation

Abstract: Hypericin (Hyp) is traditionally used as an antidepressant and antiviral agent. It selectively accumulates in spheroids and is also used as a photosensitizer in the photodynamic therapy of cancer. The present study aimed to investigate the cytotoxic effect of Hyp-mediated photodynamic therapy (Hyp-PDT) on cell growth and apoptosis of K562 leukemia cells, and to examine the underlying mechanisms. Hyp-PDT was performed with different light intensities (0.1, 0.3 and 0.5 mW/cm2), different concentrations of Hyp (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Paraptosis was initially described as a response to ER stress, with JNK and MAPK/ERK pathways involved (15,16). These pathways are also stimulated by the photodynamic action of hypericin (6,7,26‐28). Whether MAPK effects are a cause of or a response to PDT‐related photodamage is not entirely clear.…”
Section: Resultsmentioning
confidence: 99%
“…Paraptosis was initially described as a response to ER stress, with JNK and MAPK/ERK pathways involved (15,16). These pathways are also stimulated by the photodynamic action of hypericin (6,7,26‐28). Whether MAPK effects are a cause of or a response to PDT‐related photodamage is not entirely clear.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the overexpression of pro-inflammatory cytokines during CP induction, such as TNF-, IL-1β and IL-6 may promote the allodynia of CP rats ( 18 , 26 ), and these mediators may induce the activation of JNK and extracellular signal-regulated kinase (ERK) signaling pathways, which serve important roles in the maintenance of chronic pain. IL-1β is the most important inflammatory mediator that causes pancreatic islet dysfunction and destruction, which may promote activation of JNK ( 27 29 ); previous studies have also demonstrated positive effect of TNF-α and IL-6 on JNK activation ( 30 32 ). MOR expression is mainly regulated by signaling pathways such as JNK ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used as antidepressant, antiviral, and antiretroviral agents in the past decades. [15][16][17] Recently, Hy has attracted much attention as a potent PS with substantial quantum yield, low photobleaching, a large excitation range, and negligible dark cytotoxicity. 7,17,18 However, like most PSs, Hy is highly hydrophobic and cannot dissolve in aqueous medium, which reduces its photodynamic property and shortens its circulation time in blood in vivo, thus affecting its accumulation in the tumor site and weakening the effect of PDT for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%